2021
DOI: 10.7759/cureus.17256
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Sunflower Seeds and Flax Seeds on Diabetes

Abstract: Diabetes mellitus (DM) is a metabolic syndrome that is spreading like an epidemic throughout the world without any differentiation of races and ethnic groups and has become the cause of death worldwide. It is characterized by high levels of glucose in the blood and has different types classified on the basis of varying pathophysiology. Type 1 diabetes or insulin-dependent diabetes is characterized by insulin insufficiency due to autoimmune dysfunction. Type 2 diabetes or non-insulin-dependent diabetes results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The bioactive components of sunflower seeds (chlorogenic acid) and flaxseeds (secoisolariciresinol diglucosoid) can improve insulin resistance and insulin production [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive components of sunflower seeds (chlorogenic acid) and flaxseeds (secoisolariciresinol diglucosoid) can improve insulin resistance and insulin production [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antidiabetic effect of H. annuus hydroalcoholic extract was exhibited in Choudhary study (12). In a study by Adeleke Ojo, the leaf of H. annuus exhibited antidiabetic effect via inhibition of α-amylase and α-glucosidase enzymes (13). The aim of this study was to assess the H. annuus seed extract effects on FBS, weight and body composition among patients with T2DM.…”
Section: Analysis Of H Annuus Effectsmentioning
confidence: 95%
“…While these seeds are rich in oil (36-50%) [15] and contain largely unsaturated fatty acids [16,17], the plant and its parts are endowed with abundant pharmacological potential [18], including antioxidant [12], antimicrobial [19][20][21], and cytotoxic [21] effects attributed to its metabolites (flavonoids, phenolic acids, tocopherol, saponins, alkaloids, tannins, and terpenes) and/or several phytoconstituents [20]. Additionally, while the quantitative determination of the chemical contents of the various cultivars of the seeds has revealed 23 saturated and unsaturated fatty acids with linoleic acid being the most abundant [22,23], the antidiabetic effects of the plant seed have been established in a few reports [24] as, for example, recently reviewed by Rehman et al [25], though no study has reported the antidiabetic potential of the oilseed of the plant. Moreover, since the quality and therapeutic effectiveness are known as factors which determine the oilseed's ability to lower blood cholesterol and reducing the risk of cardiovascular diseases, among others, it is important to study the therapeutic role the inherent phytoconstituents play in exhibiting or being responsible for these effects, particularly against T2D as well as the molecular mechanisms underlying their action.…”
Section: Introductionmentioning
confidence: 99%